THE RELATIONSHIP BETWEEN TEACHER PEDAGOGICAL COMPETENCE, CAREER EXPECTATIONS, AND SCHOOL INFRASTRUCTURE AND LEARNING OUTCOMES OF GRADE VI STUDENTS - Ni Putu Sukma Srijayanti; Maria Goreti Rini Kristiantari; Sandra Sukmaning Adji (Indonesian Journal of Educational Development (IJED), 2023)
This study aims to find out how much the relationship between teacher pedagogic competence, career expectations, and school infrastructure has to the learning outcomes of class VI elementary school students in Cluster III, Kediri District, Tabanan Regency. This research is ex post facto with a population of 282 students. Determination of the sample through random sampling technique in order to obtain a sample of 162 students. Data is collected through questionnaires and document study. Data analysis uses multiple regression and partial correlation. The results of the study show that: 1) there is a significant relationship between teacher pedagogical competence and student learning outcomes; 2) there is a significant relationship between career expectations and student learning outcomes; 3) there is a significant relationship between school infrastructure and student learning outcomes; and 4) taken together, there is a significant relationship between teacher pedagogical competence, career expectations, and school infrastructure with student learning outcomes.